Spatiotemporal Changes of the Phagosomal Proteome in Dendritic Cells in Response to LPS Stimulation - Pauwels, Anne-Marie (Mol Cell Proteomics, 2019)
Dendritic cells (DCs) are professional phagocytes that use innate sensing and phagocytosis to internalize and degrade self as well as foreign material, such as pathogenic bacteria, within phagosomes. These intracellular compartments are equipped to generate antigenic peptides that serve as source for antigen presentation to T cells initiating adaptive immune responses. The phagosomal proteome of DCs is only partially studied and is highly dynamic as it changes during phagosome maturation, when phagosomes sequentially interact with endosomes and lysosomes. In addition, the activation status of the phagocyte can modulate the phagosomal composition and is able to shape phagosomal functions. In this study, we determined spatiotemporal changes of the proteome of DC phagosomes during their maturation and compared resting and lipopolysaccharide (LPS)-stimulated bone marrow-derived DCs by label-free, quantitative mass spectrometry. Ovalbumin-coupled latex beads were used as phagocytosis model system and revealed that LPS-treated DCs show decreased recruitment of proteins involved in phagosome maturation, such as subunits of the vacuolar proton ATPase, cathepsin B, D, S, and RAB7. In contrast, those phagosomes were characterized by an increased recruitment of proteins involved in antigen cross-presentation, e.g. different subunits of MHC I molecules, the proteasome and tapasin, confirming the observed increase in cross-presentation efficacy in those cells. Further, several proteins were identified that were not previously associated with phagosomal functions. Hierarchical clustering of phagosomal proteins demonstrated that their acquisition to DC phagosomes is not only dependent on the duration of phagosome maturation but also on the activation state of DCs. Thus, our study provides a comprehensive overview of how DCs alter their phagosome composition in response to LPS, which has profound impact on the initiation of efficient immune responses.